Downregulation of Lung Toll-Like Receptor 4 Could Effectively Attenuate Liver Transplantation-Induced Pulmonary Damage at the Early Stage of Reperfusion - Xinjin Chi; Weifeng Yao; Ailan Zhang; Mian Ge; Jun Cai; Shaoli Zhou; Zhengyuan Xia; Gangjian Luo; Ziqing Hei (Hindawi Limited, 2015)
Acute lung injury (ALI) is a severe complication of orthotopic liver transplantation (OLT) with unclear underline mechanism. Toll-like receptor 4 (TLR4) has been identified as a key receptor mediating inflammation. We hypothesized that TLR4-mediated pulmonary inflammation may contribute to development of ALI during OLT. Patients with or without ALI were observed for serum cytokines and expression of TLR4 on peripheral blood polymorphonuclear leukocytes (PMNs). Next, rats which underwent orthotopic autologous liver transplantation (OALT) were divided into sham and model groups. Pulmonary function and the level of TLR4 expression and cytokines were analyzed. Furthermore, the role of TLR4 in OALT-mediated ALI was assessed in rats treated with TLR4-siRNA before OALT. The PMNs TLR4 expression and the serum TNF-α and IL-β level were higher in patients with ALI than those with non-ALI. Interestingly, lung TLR4 expression was significantly increased after 8 hours of OALT with increased levels of TNF-α and IL-β, which lead to lung pathological damage and an increase of lung myeloperoxidase content. Moreover, knockdown of TLR4 reduced lung cytokines release and reversed the above pathologic changes after OALT and finally improved rats' survival rate. In conclusion, TLR4 overexpression, potentially by stimulating proinflammatory cytokine overproduction, contributes to the development of ALI after OLT.